Anti-immigration conspiracy beliefs are associated with endorsement of conventional and violent actions opposing immigration and attitudes towards democracy across 21 countries - Thomas, Emma F.; Stothard, Christina; Besta, Tomasz; Akbas, Gulcin; Becker, Julia C.; Becker, Maja; Brik, Tymofii; Chayinska, Maria; Deguchi, Makiko; Dhakal, Sandesh; Kelmendi, Kaltrina; Kende, Anna; et al. (Communications psychology, 2025)
Despite widespread speculation that conspiracy beliefs foster anti-democratic outcomes, the empirical picture is inconsistent. To clarify this literature, we examine the relationships that conspiracy beliefs have with commitment to reactionary action and criticism of democracy, focusing on a global issue: immigration. We expected that people who believe that their government uses immigration to diversify the population against citizens’ wishes (anti-migration conspiracy beliefs) would be more committed to conventional and violent action to oppose immigration, and more critical of democracy. However, societal-level factors – economic performance and democratic functioning – were expected to influence (strengthen, weaken) these links. As hypothesized, multi-level analyses ( N = 4353) from 21 countries revealed that economic prosperity attenuated the positive link between anti-migration conspiracy beliefs and commitment to reactionary action. Paradoxically, more democratic societies evidenced stronger links between conspiracy beliefs and conventional (but not violent) action to oppose immigration. Thus, more democratic societies appear to invite conventional forms of action to oppose immigration which may, in turn, weaken democratic norms of inclusion. Results highlight the interplay of individual- and societal-level factors underlying illiberal movements. The link between conspiracy beliefs and reactionary movements that promote intolerance and undermine democracy was investigated in 21 countries. Economic prosperity and democratic functioning moderated the positive link between anti-migration conspiracy beliefs and commitment to reactionary action.